2020 3rd International Seminar on Research of Information Technology and Intelligent Systems (ISRITI) 2020
DOI: 10.1109/isriti51436.2020.9315484
|View full text |Cite
|
Sign up to set email alerts
|

Indonesian Stock Price Prediction including Covid19 Era Using Decision Tree Regression

Abstract: Predicting stock prices is an interesting field in DataMining. There are many variables affecting stock prices. Especially in this covid19 era which impacts in economy, the stock prices become unpredictable. Telecommunications companies are observed in this research as it is one of the sectors that's still very much in demand in this pandemic situation. Fundamental data will be used to predict the Indonesian telecommunications stock price. Regression techniques will be used as the proposed model. The correlati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 17 publications
0
7
0
1
Order By: Relevance
“…However, the accuracy of the white-box model is limited due to the harsh operating environment and the complex model structure [ 28 ]. Hindrayani et al observed the data stocks of telecommunication companies and generalized the inference for each prediction decision for each company stock by constructing a decision tree model, and the final results obtained the smallest mean absolute percentage error [ 29 ]. Shakeri et al proposed an expert system based on fuzzy rules.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, the accuracy of the white-box model is limited due to the harsh operating environment and the complex model structure [ 28 ]. Hindrayani et al observed the data stocks of telecommunication companies and generalized the inference for each prediction decision for each company stock by constructing a decision tree model, and the final results obtained the smallest mean absolute percentage error [ 29 ]. Shakeri et al proposed an expert system based on fuzzy rules.…”
Section: Literature Reviewmentioning
confidence: 99%
“…DT-R is a regression method in which model development is conducted using a tree structure that has root, branches, and leaf nodes [25]. The decision tree is completed by selecting the appropriate attribute with attribute selection measures (ASM).…”
Section: Machine Learning Testingmentioning
confidence: 99%
“…The result differentiates between regression trees and categorization trees, although the classification trees are similar to regression trees constructed from Root, Node, and Leaf. A regression tree's output is a continuous or real value rather than a class [11].…”
Section: Decision Treementioning
confidence: 99%